Pengaruh Rasio Profitabilitas dan Rasio Aktivitas Terhadap Perubahan Laba Pada PT. Astra Agro Lestari Tbk - Yeni Rosa Damayanti; Alwi Alwi (Jurnal Manajemen Riset Inovasi, 2023)
This research aims to determine the effect of profitability ratios and activity ratios on profit growth at PT. Astra Agro Lestari during the 2012-2021 period. The independent variables used to measure profitability ratios are return on investment (ROI) and Gross Profit Margin (GPM), the independent variables used to measure activity ratios are measured by Receivable turnover (RTO) and Fixed asset turnover (FATO). The dependent variable used in this research is profit growth. The data in this study uses secondary data, namely financial reports for 10 years, starting from 2012-2021 at PT. Astra Agro Lestari Tbk. The data analysis techniques used are the classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination t test and f test. The results of research using the t test show that the return on investment (ROI) variable has no significant effect on profit growth, the Gross Profit Margin (GPM) variable has no significant effect on profit growth, the Receivable Turnover (RTO) variable has no significant effect on profit growth and the Fixed variable asset turnover (FATO) has no significant effect on profit growth.